Operando Study of Thermal Oxidation of Monolayer MoS2. Issue 9 (1st March 2021) - Park, Sangwook; Garcia‐Esparza, Angel T.; Abroshan, Hadi; Abraham, Baxter; Vinson, John; Gallo, Alessandro; Nordlund, Dennis; Park, Joonsuk; Kim, Taeho Roy; Vallez, Lauren; Alonso‐Mori, Roberto; Sokaras, Dimosthenis; et al.
Abstract: Monolayer MoS2 is a promising semiconductor to overcome the physical dimension limits of microelectronic devices. Understanding the thermochemical stability of MoS2 is essential since these devices generate heat and are susceptible to oxidative environments. Herein, the promoting effect of molybdenum oxides (MoO x ) particles on the thermal oxidation of MoS2 monolayers is shown by employing operando X‐ray absorption spectroscopy, ex situ scanning electron microscopy and X‐ray photoelectron spectroscopy. The study demonstrates that chemical vapor deposition‐grown MoS2 monolayers contain intrinsic MoO x and are quickly oxidized at 100 °C (3 vol% O2 /He), in contrast to previously reported oxidation thresholds (e.g., 250 °C, t ≤ 1 h in the air). Otherwise, removing MoO x increases the thermal oxidation onset temperature of monolayer MoS2 to 300 °C. These results indicate that MoO x promote oxidation. An oxide‐free lattice is critical to the long‐term stability of monolayer MoS2 in state‐of‐the‐art 2D electronic, optical, and catalytic applications. Abstract : Operando X‐ray absorption spectroscopy elucidates molybdenum oxide (MoO x ) impurities' effect on the thermochemical stability of monolayer MoS2 . The thermal oxidation onset of as‐grown monolayer MoS2 is as low as 100 °C with MoO x present, overestimated by >150 °C in the literature (T ≥ 250 °C, t ≤ 1 h). Removal of MoO x increases the oxidation onset temperature to 300 °C.